2021
DOI: 10.1075/ts.20048.but
|View full text |Cite
|
Sign up to set email alerts
|

Targeted individuals

Abstract: This article argues that researchers in Translation Studies may proactively aim to understand the consequences of an envisaged merger between targeted advertising and automated translation. Functional translation software is widely available online, and several platforms now perform instant translation, sometimes without asking the user whether this is required. Indeed, the user’s main language is known to various applications, which keep track of this information along with other settings and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…They found that children's first encounters with MT tended to take place outside of school, which suggests that younger generations start using MT organically rather than in a structured educational environment. Buts (2021) does not look at current MT uses, but rather at future purposes that the technology may serve in advertising. His work touches on MT's persuasive role although, in contrast to the present article, it does not focus on different types of MT use or of human-MT relations.…”
Section: Research On Machine Translation and Societymentioning
confidence: 99%
“…They found that children's first encounters with MT tended to take place outside of school, which suggests that younger generations start using MT organically rather than in a structured educational environment. Buts (2021) does not look at current MT uses, but rather at future purposes that the technology may serve in advertising. His work touches on MT's persuasive role although, in contrast to the present article, it does not focus on different types of MT use or of human-MT relations.…”
Section: Research On Machine Translation and Societymentioning
confidence: 99%